Stimulation of macrophages by immunobiotic Lactobacillus strains: influence beyond the intestinal tract - Marranzino, Gabriela (2012)
Lactobacillus rhamnosus CRL1505 (Lr1505), L. rhamnosus CRL1506 (Lr1506) and L. casei CRL431 (Lc431) are able to stimulate intestinal immunity, but only Lr1505 and Lc431 are able to stimulate immunity in the respiratory tract. With the aim of advancing the understanding of the immunological mechanisms involved in stimulation of distant mucosal sites, this study evaluated the effects of orally administered probiotics on the functions of alveolar and peritoneal macrophages. Compared to a control group, these three lactobacilli were able to significantly increase phagocytic and microbicidal activities of peritoneal macrophages. After intraperitoneal challenge with pathogenic Candida albicans, mice treated with immunobiotics had significantly lower pathogen counts in infected organs. Moreover, lactobacilli- treated mice had a stronger immune response against C. albicans. On the other hand, only Lc1505 and Lc431 were able to improve activity of and cytokine production by alveolar macrophages. Only in these two groups was there better resistance to respiratory challenge with C. albicans, which correlated with improved respiratory immune response. The results of this study suggest that consumption of some probiotic strains could be useful for improving resistance to infections in sites distant from the gut by increasing the activity of macrophages at those sites.